Solenoid as a Wheeled KRSBI Robot Kicking Mechanism - Nurimam, Ahmad; Puriyatno, Riky Dwi (Signal and Image Processing Letters, 2022)
Some types of kickers used are kicker mechanisms using spring, pneumatic, and solenoid. One of the uses of the magnetic field is to use a solenoid as a kicking mechanism in a robot, the magnetic field generated from the solenoid is able to move the plunger or iron core, designing the tool using copper weighing 2 kg. The problem faced is that the kick is not far away and the effects of the electromagnetic field generated from the solenoid can interfere with the electronic system on the robot. In this study, making a solenoid with the middle dimensions on the solenoid to 41 mm and the diameter of the plunger to 38 mm and using a cover with an iron faraday cage method with aÂ  Â thickness of 2 mm to minimize the magnetic field generated from the solenoid. In this study, the mechanism solenoid consists of 1 mm enamel wire and has a copper winding with a total of 1210 windings, in the power supply of a 12V Li-Po battery which is stepped up in its voltage to 400V and stored in a capacitor using a capacity of 5600 Î¼F. By applying a solenoid voltage of 400V and a current of 4 A and being able to produce kicks with a distance of more than 6.68 meters, the height of which is able to pass through obstacles or obstacles.